Excellent data retention characteristic of Te-based conductive-bridge RAM using semiconducting Te filament for storage class memory. (March 2019) - Lee, Sangmin; Song, Jeonghwan; Lim, Seokjae; Chekol, Solomon Amsalu; Hwang, Hyunsang
Highlights: The virgin resistance and forming voltage are decreased with increasing Zr composition in Zr x Te 1−x (0.5 ≦ x ≦ 0.7) and decreasing electrolyte thickness. The temperature-dependent resistance of the formed CF in Te-based CBRAM shows semiconducting behavior and a gradual change of conductance lower than 1.0 G0 in the erase step. Activation energy for the out-diffusion of Te atoms does not contribute significantly to the excellent retention characteristics of Te-CBRAM. Abstract: In this work, we explore the electrical properties and data retention of Te-based conductive-bridge random-access memory (CBRAM) of Zr x Te 1−x /Al2 O3 /Pt cells. The virgin resistance and forming voltage are decreased with increasing Zr composition (0.5 ≦  x  ≦ 0.7) and decreasing electrolyte thickness. The resistance of the conductive filament (CF) formed in the Te-CBRAM shows semiconducting behavior that is decreased with increasing temperature, whereas a Cu-based CBRAM shows metallic behavior. Furthermore, the conductance change of Te-based CBRAM, during the filament dissolution step, occurs with lower conductance units than those of Cu/Ag-based CBRAM. The most differentiable characteristics of both devices are the data retention. Te-based CBRAM shows better data stability at high temperature (150 °C) than Cu-based device. Accelerated tests (250, 270, and 300 °C) were performed to understand the data retention of the Te-CBRAM, yielding excellent retention characteristics (10 years at 177 °C) despite its relatively low activation energy ( Ea, 1.07 eV) than Cu/Ag- based devices. We believe that the excellent retention properties of Te-based devices are more influenced by the wide effective CF size than by Ea .